2021
DOI: 10.1111/febs.15845
|View full text |Cite
|
Sign up to set email alerts
|

The largely unexplored biology of small proteins in pro‐ and eukaryotes

Abstract: The large abundance of small open reading frames (smORFs) in prokaryotic and eukaryotic genomes and the plethora of smORF-encoded small proteins became only apparent with the constant advancements in bioinformatics, genomic, proteomic and biochemical tools.Small proteins are typically defined as proteins of less than 50 amino acids in prokaryotes and of less than 100 amino acids in eukaryotes and their importance for cell physiology and cellular adaptation is only beginning to emerge. In contrast to antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 267 publications
(392 reference statements)
0
43
0
Order By: Relevance
“…Meanwhile, the functions of some SEPs in, for example, cell division, membrane transport, embryonic development, or cell death have been elucidated. Different biological functions of SEPs have been reviewed [12,15,93,94].…”
Section: Ptmsmentioning
confidence: 99%
“…Meanwhile, the functions of some SEPs in, for example, cell division, membrane transport, embryonic development, or cell death have been elucidated. Different biological functions of SEPs have been reviewed [12,15,93,94].…”
Section: Ptmsmentioning
confidence: 99%
“…However, a recent study has demonstrated that under stress conditions, the hyper-phosphorylated guanine nucleotides ppGpp and pppGpp bind to the GTPase domains of both SRP and FtsY and prevent the formation of a functional targeting complex 91 . This is intriguing, because many small membrane proteins, such as YohP, are upregulated when cells encounter stress conditions [107][108][109][110] , but the simultaneous (p)ppGpp accumulation would prevent their membrane insertion by the SRP-pathway 96 . mRNA targeting and SRP-independent protein insertion, as shown here for YohP, could provide a solution to this conundrum and allow for the insertion of stress-response proteins even when the SRP pathway is impaired (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both these events can respond to intracellular stresses 7779 . Curiously, it has already been proposed that SEP expression may be an integral part of the cellular “stress response” 80 . The link to developmental functions is also intriguing, because promoter switching and translational reprogramming are key events during differentiation in metazoans 81, 82 .…”
Section: Discussionmentioning
confidence: 99%